Endoproteolysis of cellular prion protein by plasmin hinders propagation of prions - Mays, Charles E.; Trinh, Trang H. T.; Telling, Glenn; Kang, Hae-Eun; Ryou, Chongsuk (Frontiers in Molecular Neuroscience, 2022)
Many questions surround the underlying mechanism for the differential metabolic processing observed for the prion protein (PrP) in healthy and prion-infected mammals. Foremost, the physiological α-cleavage of PrP interrupts a region critical for both toxicity and conversion of cellular PrP (PrPC) into its misfolded pathogenic isoform (PrPSc) by generating a glycosylphosphatidylinositol (GPI)-anchored C1 fragment. During prion diseases, alternative β-cleavage of PrP becomes prominent, producing a GPI-anchored C2 fragment with this particular region intact. It remains unexplored whether physical up-regulation of α-cleavage can inhibit disease progression. Furthermore, several pieces of evidence indicate that a disintegrin and metalloproteinase (ADAM) 10 and ADAM17 play a much smaller role in the α-cleavage of PrPC than originally believed, thus presenting the need to identify the primary protease(s) responsible. For this purpose, we characterized the ability of plasmin to perform PrP α-cleavage. Then, we conducted functional assays using protein misfolding cyclic amplification (PMCA) and prion-infected cell lines to clarify the role of plasmin-mediated α-cleavage during prion propagation. Here, we demonstrated an inhibitory role of plasmin for PrPSc formation through PrP α-cleavage that increased C1 fragments resulting in reduced prion conversion compared with non-treated PMCA and cell cultures. The reduction of prion infectious titer in the bioassay of plasmin-treated PMCA material also supported the inhibitory role of plasmin on PrPSc replication. Our results suggest that plasmin-mediated endoproteolytic cleavage of PrP may be an important event to prevent prion propagation.